Epidemiology of pancreatic cancer in the XX and the beginning of the XXI century - A. M. Sidorenko; A. I. Shevchenko; I. S. Kugayenko (Zaporozhye State Medical University, 2013)
Pancreatic cancer is responsible for 227,000 deaths per year, and is the eighth most common cause of death from cancer in both sexes combined, a relative position is higher than for incidence (thirteenth) because of the very poor prognosis (the mortality / incidence ratio is 98%). Survival rates are 2% to 5% in cancer registries for the developed and developing countries. Such disappointing results of treatment are explained by early pancreatic cancer metastasis to regional lymph nodes, bone marrow and liver. The purpose of the survey was published data on the problem of morbidity, mortality, and the results of treatment of pancretic cancer. We also consider the etiology and prognosis of the disease. The incidence and mortality of pancreatic cancer increases in the United States and Europe, including Ukraine, where incidence and mortality rates are between 5 and 12 per 100000 of population. In the Soviet Union in the official statistical reporting documents pancreatic cancer is not detected as a separate nosological form. Disparate epidemiological data is the result of some authors. In the twenty-first century the pancreatic cancer causes more than 4000 deaths in Ukraine per year, or almost as much as the annual new cases of pancreatic cancer detected. For example, in 2011 in Ukraine 4885 new cases of pancreatic cancer were registered and 4137 people died. The male mortality rate is 6.2 per 100 thousand of the male population, women - 4.3 per 100 thousand women (world standard). In Ukraine relative frequency of pancreatic cancer in men was 4.7% (6th place), women - 4.5% (9th place)in the structure of mortality from malignant tumors. The incidence of pancreatic cancer in the world is uneven: 2.2 cases per 100 thousand of population in India, Kuwait, Singapore, and 4 cases per 100 thousand of population in the countries of southern Europe, in Japan, 11 new cases of pancreatic cancer per 100 thousand people in the United States, 12.5 cases per 100 thousand people in Sweden. In Ukraine, the incidence is 5.9 per 100 thousand population (world standard). Most cases and deaths (61%) occur in developed countries, where incidence and mortality rates are between 7 and 9 per 100,000 in men and 4.5 and 6 per 100,000 in women, with lower rates in developing countries. This probably reflects diagnostic capacity rather than etiology. Among the developing countries, the highest rates are observed in Central and South America. Among the different ethnic groups, the highest level of incidence of pancreatic cancer was fixed among the indigenous inhabitants of the Hawaiian Islands, among African Americans in San Francisco (USA), among Maori in New Zealand and Africans in Bulawayo. In the U.S., African-Americans sickness rate ofpancreatic cancer is higher than in other ethnic groups. Pancreatic cancer is more common in people with middle and old age: the incidence and mortality rates of pancreatic cancer are rising sharply after age 55, and they are highest in 70-74 years. Little is known about the etiology of this cancer, although tobacco smoking increases the risk. The surgical method is the only radical method and the most effective in the treatment of pre-clinical stages of pancreatic cancer. Recent experience has shown that a CT scan of the abdomen and serum marker CA 19-9 now are reliable methods of screening for pancreatic cancer.